Kewenangan Pejabat Pengganti Kepala Daerah Dalam Penyelenggaraan Pemerintah Daerah Dari Perspektif Peraturan Perundang-Undangan - Wahyudi, Amar; Syam, Fauzi; Mushawirya, Rustian (Fakultas Hukum Universitas Jambi, 2022)
This research is motivated by the existence of inconsistencies in norms, ambiguity of norms, and differences in interpretation or designation of Substitute Regional Heads who are unable to carry out tasks. Regional Government Law and its differences with the authority of Substitute Officials in the Government Administration Law.â€The research methodâ€usedâ€is normative research â€œusingâ€ (Statute Approach)â€and (Conceptual Approach)â€. Legal materials in this study include primary legal materials, secondary legal materials,â€and tertiary legal materials. Theâ€results â€œof this studyâ€conclude that the Substitute Official Arrangement in the Government Administration Act actually only applies to the replacement of Administrative Positions so that it cannot be used to replace the Regional Head Position as a political position. There are only 2 types of Substitute Officials in the Government Administration Law, namely: (a) Daily Implementing Officers (Plh) and (b) Task Executing Officers (Plt). There are 4 types of Nomenclature of Substitute Officials in the Regional Government Law and its implementing regulations, namely: (a) Acting Regional Head (Plt KDH); (b) Acting Regional Head (Pj KDH); (c) Temporary Regional Head (Pjs KDH); and (d) Daily Implementing Regional Head (Plh KDH) It is hoped that later the relevant Government will issue a new regulation or explanatory regulation related to the Executing Tasks, Daily Executors, Temporary Acting and Acting.